A preliminary analysis of flat-gravel transport over a sandy beach, Pehuén Co, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Pehuén Co Beach, on the southwest coast of the Buenos Aires Province (Argentina), provides an example of an heterogeneous (mixed sand-gravel) sediment beach with gravels of the most diverse size and origin. Over 40% of the pebbles are carbonate flat gravels. Field observations included beach profiles, measurements of wave generated currents with an acoustic currentmeter (ADV), videos of 5 x 5 m grid located on the swash zone during inundation from a nearby tower. Video films where rectified and analyzed using PIV and wavelets. Based on the results, we demonstrated that flat gravels can be easily transported upbeach distances in excess of 5 m in about 1.5 h. This period corresponds to the high tide situation and covering the steepest beachface segment. Wave conditions during the experiment corresponded to low breaker height and short periods, but by no means they could be considered as storm waves demonstrating that gravels can be transported even by saltation during fair weather conditions.
Keywords: Heterogeneous Beaches, Gravel Transport, Wave Runup, Pehuén Co Beach, Argentina.